Trend in Sensitivity of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Serology One Year After Mild and Asymptomatic Coronavirus Disease 2019 (COVID-19): Unpacking Potential Bias in Seroprevalence Studies. (13th January 2022) - Bailie, Christopher R; Tseng, Yeu Yang; Carolan, Louise; Kirk, Martyn D; Nicholson, Suellen; Fox, Annette; Sullivan, Sheena G
Abstract: A key aim of serosurveillance during the coronavirus disease 2019 (COVID-19) pandemic has been to estimate the prevalence of prior infection, by correcting crude seroprevalence against estimated test performance for polymerase chain reaction (PCR)-confirmed COVID-19. We show that poor generalizability of sensitivity estimates to some target populations may lead to substantial underestimation of case numbers.